“Analisa sistem jaringan Distribusi Air Bersih Pada Bangunan Gedung Rumah Sakit Umum Daerah Abdul Wahab Sjahranie“ - SUTRISNO, TRI (KURVA S JURNAL MAHASISWA, 2012)
Clean Water [is] water which [is] [is] needed to fulfill the hospital requirement, covering water to cook and drink the, water take a bath the, water clean and also to clean the hospital. While such with the processing [is] the effort - technical effort [done/conducted] to denature - nature of a[n Iihat vitamin. Matter is important its meaning for clean water, because with the existence of this processing hence will [in] getting a[n clean water fulfilling clean water standard [is] which have been determined. clean Water existence very needed to to support the economic growth rate along with the increasing of resident requirement and also publik utulities. Clean amount of water required [in] town - metropolis [is] generally laboured by Drinking Water Company ( PAM) [of] publik ownwrship channelled [by] kerumah resident of[is totality town, and recognized by society as water work water. Make-Up of clean water quality by way of performing [a] management to water to be needed [by] as clean water [is] flat flatly needed especially if the water. such processing can be started from very simple up to complete and skilled processing, as according to tingakat dirtiness from the water source. dirty progressively hence progressively heavily also required processing, and more and more manner of Iihat vitamin [of] pencemar will more and more also technique - technique which [is] [is] needed to [by] the mengolah water, [so that/ to be] can be exploited [by] as clean water. To reach the the effort hence require to be realized by way of Analysis of system of Clean Water Distribution network. Basically Analyse this intended to fulfill healthy clean amount of water required as according to clean water standard [is] which have been specified, what in the end aim to also to increase prosperity and society health, especially which deal with environmental condition balance.